2002
DOI: 10.1091/mbc.01-12-0579
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Transport from the Golgi Complex to the Endoplasmic Reticulum by CDC42 and N-WASP

Abstract: Actin is involved in the organization of the Golgi complex and Golgi-to-ER protein transport in mammalian cells. Little, however, is known about the regulation of the Golgi-associated actin cytoskeleton. We provide evidence that Cdc42, a small GTPase that regulates actin dynamics, controls Golgi-to-ER protein transport. We located GFP-Cdc42 in the lateral portions of Golgi cisternae and in COPI-coated and noncoated Golgi-associated transport intermediates. Overexpression of Cdc42 and its activated form Cdc42V1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 83 publications
5
136
0
4
Order By: Relevance
“…This is consistent with previous reports that have indicated that activation of Cdc42 is needed mainly to control membrane transport events in the post-Golgi space (Kroschewski et al, 1999;Musch et al, 2001). In addition, Cdc42 has been shown to participate in retrograde transport from the Golgi complex to the ER (Luna et al, 2002). Whether or not FGD1 also acts in this Cdc42-mediated transport step at the ER/ Golgi interface remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous reports that have indicated that activation of Cdc42 is needed mainly to control membrane transport events in the post-Golgi space (Kroschewski et al, 1999;Musch et al, 2001). In addition, Cdc42 has been shown to participate in retrograde transport from the Golgi complex to the ER (Luna et al, 2002). Whether or not FGD1 also acts in this Cdc42-mediated transport step at the ER/ Golgi interface remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This could affect the dynamic behavior of TGN membranes (Musch et al, 2001) and/or the short-range motility of PGCs (or their precursors) in the Golgi area, with this motility appearing to be mediated by myosin VI and to be required for cargo export toward the cell surface (Buss et al, 1998). Golgi-associated Cdc42 effectors, such as WASP (Luna et al, 2002) and IQGAP (McCallum et al, 1998), are also likely be involved in the regulation of actin dynamics at the Golgi complex, and in addition, PAK1 might control the movement of PGCs via the phosphorylation of myosin VI (Buss et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Cdc42 also associates strongly with Golgi membranes, where it regulates both retrograde transport from the Golgi to the ER [14] and exit from the trans-Golgi network (TGN) [15]. Early studies revealed that association of Cdc42 with the Golgi was sensitive to BFA, suggesting that Arf activation was necessary for Cdc42 recruitment [16].…”
Section: Arf Regulation Of Actin Assembly In the Golgimentioning
confidence: 99%
“…Moreover, a role for actin dynamics is strongly suggested by the involvement of some actin cytoskeleton regulatory molecules and actin-binding or actin-associated proteins in the formation and/or movement of transport intermediates. Those include Cdc42 and some downstream signalling effectors such as N-WASP, Arp2/3, and LIMK1 [Erickson et al, 1996;Fucini et al, 2002;Luna et al, 2002;Carreno et al, 2004;Chen et al, 2004a;Matas et al, 2004;Rosso et al, 2004], Cdc42-GAP protein [Dubois et al, 2005], the Cdc42-related protein TC10 [Kanzaki et al, 2002], mAbp1 [Fucini et al, 2002;Kessels and Qualmann, 2002], non-muscle myosin II [Heimann et al, 1999;Duran et al, 2003], Golgi-specific spectrin and ankyrin isoforms [Beck et al, 1994[Beck et al, , 1997Deverajan et al, 1996], the spectrin family member syne-1 [Gough et al, 2003[Gough et al, , 2004, syndapins Qualmann, 2002, 2004], the Sla2/Huntingtin-interactin protein 1 member Hip1R [Carreno et al, 2004] and cortactin [Cao et al, 2005]. Collectively, these data indicate that a complex molecular machinery regulates actin dynamics in Golgi membranes, which seems to be involved in Golgi-associated transport events.…”
Section: Introductionmentioning
confidence: 99%